Development of technologies and equipment for manufacturing sand‑resin cores for high‑volume foundry production - D. M. Golub; S. N. Grechanik; A. V. Pashkevich; S. L. Rimoshevsky; D. A. Prokopchuk (Литьë и металлургия)
The article discusses the scientific and technical developments of OJSC “BELNIILIT” aimed at the creation of modern technologies and equipment for the machine‑based production of sand‑resin cores for foundries. It outlines the approaches of specialists in the design of core machine assemblies, mechanisms, and tooling. The paper presents practical implementation results of core‑making equipment, examples of complex sand cores produced using OJSC “BELNIILIT” machinery at various mechanical engineering enterprises, and highlights the prospects for future development in this field.